2012
DOI: 10.2174/1874325001206010121
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of the Best Surgery After Single Level Anterior Cervical Spine Discectomy: A Systematic Review

Abstract: Background:The anterior cervical discectomy (ACD) is often used to treat spinal cord and nerve root compressions and the frequent use of interbody fusion (ACDF) has popularized it as a common practice associated or not with cages or plates for maintaining the intervertebral disc height.Objective:The aim of this study is to clarify the effectiveness of ACD compared with ACDF, with or without the use of anterior cervical spacer (Cage) or instrumentation with plate fixation (ACDFI).Methods:randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…As is the case with many other grafts, which are currently used in spine surgery, there are no studies with an evidence level 1 to assess the deployability of PMMA. Thus, even the widely accepted opinion on PM-MA's lesser capacity to produce fusion lacks profound evidence 52 . There is even less evidence that fused patients have a better clinical outcome than non-fused patients.…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with many other grafts, which are currently used in spine surgery, there are no studies with an evidence level 1 to assess the deployability of PMMA. Thus, even the widely accepted opinion on PM-MA's lesser capacity to produce fusion lacks profound evidence 52 . There is even less evidence that fused patients have a better clinical outcome than non-fused patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al analysed the whole spine sagittal alignment after ACDF and concluded that the fusion procedure affects the spine sagittal alignment: cervical lordosis decreased especially in patients with high cervical lordosis and the sagittal vertical axis decreased [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Central canal compromise that cannot be reached through a posterior keyhole foraminotomy can be more safely addressed with anterior revision of the ACDF or posterior laminectomy for multiple level pathology. 8,18,32,41 More aggressive attempts at resecting medially located disc material are associated with higher morbidity. 34 We have also found that recurrent radiculopathy due to disc disease at the index level is more commonly a residual stenosis rather than a true disc recurrence, which was more common at fresh level.…”
Section: Discussionmentioning
confidence: 99%